Evaluation of selected parameters of inflammation, coagulation system, and formation of extracellular neutrophil traps (NETs) in the perioperative period in patients undergoing endovascular treatment of thoracoabdominal aneurysm with a branched device (t-Branch) - Michalska, Milena; Grochowiecki, Tadeusz; Wyczałkowska-Tomasik, Aleksandra; Pączek, Leszek; Jakimowicz, Tomasz; Cacko, Andrzej; Jama, Katarzyna; Stec, Albert; Sikorska, Ewa; Nazarewski, Sławomir; Gałązka, Zbigniew (Frontiers in Cardiovascular Medicine, 2023)
Extracellular Neutrophils Traps (NETs) and their formation, known as NETosis, have become pivotal in the pathogenesis of aortic aneurysm development. This study investigates the NETosis markers with the assessment of selected parameters of inflammation and coagulation system in patients with thoracoabdominal aortic aneurysms in the pre-and postop period undergoing t-Branch stent-graft implantation. The study included 20 patients with thoracoabdominal aortic aneurysms. Three markers double-stranded DNA (dsDNA), single-stranded DNA (ssDNA), and citrullinated H3 histones (Cit-H3) were tested at three-time points from patients’ blood. The parameters of NETosis, inflammation, and coagulation system were examined in the preoperative period (within 24 h before surgery) and in the postoperative period (on the 3rd and 5th postoperative day). Free-circulating DNA (cfDNA) was isolated from the blood using the MagMAXTM Cell-Free DNA Extraction Kit. Double-stranded DNA (dsDNA) and single-stranded DNA (ssDNA) were then quantified using the Qubit dsDNA HS Assay Kit and the Qubit ssDNA Assay Kit. Cit-H3 concentration was determined by enzyme immunoassay ELISA (Cayman). The results revealed the significance of NETs secretion in response to the complex processes after stent-graft implantation. All NET markers increased shortly after surgery, with histones being the first to return to preoperative levels. The lack of normalization of dsDNA and ssDNA levels to preoperative levels by the last postoperative blood collection demonstrates NETs reorganization. The increase in the number of neutrophils was not related to the expansion of postoperative NETosis. The study reveals a new marker of NETosis, ssDNA, that has not been studied so far. The implantation of a stent graft in a patient with TAAA triggers an inflammatory response manifested by an increase in inflammatory parameters. One of the hallmarks of inflammation is the activation of neutrophil extracellular traps.